Modern solutions for diagnosis of kidney in obese children - Deekshith Battu (Journal of Science in Medicine and Life, 2024)
The study of the vascular bed by the Doppler method makes it possible in practical medicine to evaluate the intrarenal hemodynamics of the vascular bed and the functioning of the organ itself. Dopplerographic examination is scanning in the pulse Doppler, color and power mapping modes. The pulse Doppler mode helps to evaluate the qualitative characteristics and speed indicators of renal hemodynamics. Today, the methods of color Doppler mapping and power Doppler have begun to be widely used to detect nephropathy. The main goal of these methods is to evaluate the dislocation of intrarenal vessels, their transverse diameter, as well as the degree of blood supply to the kidney tissue [3,6.8]. Power Doppler allows visualization of low-velocity blood flow and is recommended for use in assessing normal intrarenal vascular network and identifying areas of ischemia in the kidneys [7,10,12]. Due to the use of power Doppler in 3D mode , it is recommended by scientists for visualization of small renal vessels, up to numerous interlobular arteries [14-16].